Mercantilização do espaço rural pelo turismo: uma leitura a partir do município de Cairu-Ba - Thévenin, Julien Marius Reis (2009)
The nature becoming scarce, for its appropriation and consumption inside of the logic of accumulation in the hegemonic way of production, as well as for the industrialization and urbanization as development standard, has been submitted to a new form of value aggregation through the contemplative consumption of the landscape. That way, the tourism activity, as stage of the extended accumulation of the capital has appealed to the rural space, cradle of the remaining natural beauty. Transforming natural landscapes into consumption products and the littoral rural space in a scenery of development and dissimulation of hope for intermediary of public politics directed toward the tourism. Aggravating a conflict establishes between the place and the world, of where it comes a loaded ratiocinator process of ideological content that arrives at each place with objects and norms established to serve them. When analyzing the city of Cairu, that it is find inserted in this process, it observes that with the installation of the tourist economy has an acceleration of the reproduction of the place under the molds of the society urban-industrial. The values that had given support to the tourism for its scarcity (natural beauties, tranquility, native culture), quickly pass to be substituted, for the contradictions produced for the social system and denied by the urban society, generating a great depreciation of the place and the proper fixed capital. Where the only real form of overcoming of this contradictory movement it is find to beyond of the capital.